The role of blood donation on wheels in the blood collection chain operational logistics during the first wave of coronavirus disease 2019 pandemic - Suchet Sachdev; Nippun Prinja; Sangeeta Kumari; Lakhvinder Singh; Divjot Singh Lamba; Hari Krishan Dhawan; Ratti Ram Sharma (Asian Journal of Transfusion Science)
BACKGROUND AND OBJECTIVES: The blood collection agencies (BCAs) employ two major logistical modes of conduct for outdoor blood collection. First, the collection agency walks to the donor’s preferred location for routine blood donation drives. Second, the drive is conducted using a heavy-duty vehicle having all the facilities for blood donation in it – Blood Donation on Wheels – hereinafter referred to as mobile blood drive (MBD). The study aimed to review the role of MBDs during the coronavirus disease 2019 (COVID-19) pandemic. MATERIALS AND METHODS: This was a retrospective analysis of data concerning the blood collection at the outdoor blood donation drives such as the number of drives, blood donations in voluntary (total outdoor), routine blood drive (RBD), and MBDs during the COVID-19 pandemic with respect to referent data. RESULTS: There was a trend in the increase in MBDs (43.3% in 2020 vs. 35.6% in 2019), with odds of 1.38 (confidence interval [CI]: 0.99–1.9), P = 0.05, during the pandemic. There was a statistically significant increase in contribution in terms of blood donations from MBDs (25.8% in 2020 vs. 19.5% in 2019), with odds of 1.43 (CI: 1.4–1.5), P < 0.05, during the pandemic. There was a statistically significant reduction in the rates of vasovagal reactions in blood donors donating blood at voluntary blood drives, RBD, and MBDs during the pandemic, in comparison with the referent data. CONCLUSION: The blood donation on wheels compliments the public outreach efforts of the BCAs, both in terms of the organization of the outdoor blood donation drives and the blood donations obtained thereof.